Vitellogenin2: spermatozoon specificity and immunoprotection in mud crabs. Issue 3 (September 2016) - Yang, Ya'nan; Zheng, Biqi; Bao, Chenchang; Huang, Huiyang; Ye, Haihui
Abstract : As the precursor of vitellin (Vn), vitellogenin (Vg) has initially been considered as a female-specific protein involved in vitellogenesis, while it was also present in males induced by hormones or organs manipulation. Distinct from vtg1 we previously found in female mud crab Scylla paramamosain, vtg2 was intriguingly detected in male testis under normal physiological conditions in this study. Sequence analysis showed that vtg2 and vtg1 were actually two isoforms of Vg caused by different types of alternative splicing. PCR and in situ hybridization analysis revealed that vtg2 was localized only in the testicular spermatozoa, while Vn was detected in both the spermatozoa of the testis and seminal vesicle. Therefore, we speculated that Vn was initially translated in testicular spermatozoa, then migrated with spermatozoa, and finally stored in the seminal vesicle, where spermatozoa gradually accomplished maturation. We presumed that vtg2 /Vn might act as an immune-relevant molecule in the male reproduction system. In the subsequent experiment, the expression of vtg2 /Vn in testis was significantly induced in response to lipopolysaccharide (LPS) and lipoteichoic acid (LTA) injection at both transcriptional and translational levels. In the light of the results presented above, we deemed that vtg2 /Vn is a novel candidate of immune-relevant molecules involved in immunoprotection during the spermatozoon maturation, and this research helps to open a new avenue for further exploring the role of Vg.